Dernières explorations en Asie et dans les régions polaires 1880 / dessinée par J. Hansen. - Hansen, Jules, 1849-1931. http://id.loc.gov/authorities/names/n2005073022 http://viaf.org/viaf/sourceID/LC|n2005073022 (UM Clark Library Maps, 1881)
Relief shown by hachures.; Names of explorers are in red.; Shows the routes of explorers in the Arctic region and Asia. 1 map : col. 26 x 26 cm.